2010
DOI: 10.1111/j.1556-4029.2010.01595.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Histological Staining on the Analysis of Human DNA from Archived Slides*

Abstract: Archived slides of cell smears treated with histological stains for sperm detection are often the only source of DNA available when cold cases are reopened. There have been conflicting reports as to the negative effects of particular histological stains on DNA recovery and quality from human cells, making stain selection an important consideration for forensic laboratories. This study investigates the effect of several staining systems on DNA recovery from histological slide samples stored from 0 to 10 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…There have been conflicting results as to whether particular histological stains are better or worse for DNA testing thus making stain selection an important consideration for forensic laboratories (17,18). One study found that Christmas Tree and Hematoxylin and Eosin stains do not have different effects on DNA quality after 10-week storage of slides (17). Sanders et al used a modified H&E staining method with reduced exposure times, in conjunction with laser microdissection and STR analysis and demonstrated adequate sperm identification and improved PCR product acquisition compared to other evaluated staining protocols (19).…”
Section: Discussionmentioning
confidence: 99%
“…There have been conflicting results as to whether particular histological stains are better or worse for DNA testing thus making stain selection an important consideration for forensic laboratories (17,18). One study found that Christmas Tree and Hematoxylin and Eosin stains do not have different effects on DNA quality after 10-week storage of slides (17). Sanders et al used a modified H&E staining method with reduced exposure times, in conjunction with laser microdissection and STR analysis and demonstrated adequate sperm identification and improved PCR product acquisition compared to other evaluated staining protocols (19).…”
Section: Discussionmentioning
confidence: 99%
“…The NF-PICS or Christmas Tree stain is one of the most widely used for histological tests for the identification of sperm in sexual assault cases ( 10 ). With this stain it is possible to color both the post-acrosomal region of the sperm head, that stains pink, and the acrosome itself, that stains light pink, while cell debris are colored green, allowing easy differentiation of spermatozoa from cellular debris and thus facilitating the reading of the slide.…”
Section: Discussionmentioning
confidence: 99%
“…This method of diluting the specimen is preferable to using a premixed dilution and minimizes cell-sampling errors, and should be used on specimens in which “no spermatozoa” were detected in a wet preparation. After centrifugation the cells are deposited in a uniform monolayer in a compact area (32mm 2 ) and even with the use of stains such as nuclear fast red and picroindigocarmine (described as NF-PICS or Christmas Tree stain; Sigma-Aldrich, St. Louis MO, USA) ( 9 , 10 ), is not always easy to identify isolated sperm heads owing to the large amount of cellular debris. Therefore, our group has developed a simple and cost-effective technique as an alternative to the Cytospin method: the microcentrifugation technique to confirm azoospermia (Labnet, Woodbridge NJ, USA).…”
Section: Introductionmentioning
confidence: 99%
“…The DNA damaging effect of hematoxylin has been described by some authors [3,4,5]. However, more recent studies describe no significant differences between the quality of DNA obtained from slides stained with hematoxylin versus unstained material [6,7], but these latter studies do not specifically look at samples that have been archived for long periods of time. Although additional studies are warranted to investigate the variation among tissue stains in the preservation of DNA in archived material, we have observed that, despite lower quality, testing can be successfully performed in most cases, regardless of the stain used.…”
Section: Protocolmentioning
confidence: 94%